Symphonic concert life and concert venues in Tokyo 1868–1945 - Büttner, Clemens (Logos, 2022)
In this survey, the development of the public concert life in Tokyo from the beginning of the Meiji Era in 1868 to the end of the Second World War is examined, based on an analysis of performance venues for symphonic concerts. It will be shown that the analysis of the architectural and acoustic conditions of performance and reception of symphonic music contribute to the understanding of the social and cultural conditions of the time. The specific preconditions as well as apparent references to European or American prototypes regarding the performance venues will be identified. This survey intends to document all venues that have been used for symphonic concerts before 1945 in Tokyo, regarding their form, size, capacity and acoustics. For the investigation of the acoustic conditions, a set of room acoustic parameters are employed. Since most of the relevant rooms do not exist anymore in their original condition, CAD models are generated as input for a room acoustics simulation software to derive the room acoustic parameters for the unoccupied and the occupied cases. The size of the orchestras are investigated based on historical sources to describe the relationship of sound source, enclosure and audience.